2020
DOI: 10.1002/csc2.20066
|View full text |Cite
|
Sign up to set email alerts
|

Comparing yield trial locations based on their elicited expressions of genetic variance among soybean cultivars

Abstract: Main considerations for yield trial site selection are the ability to discriminate among genotypes, minimize redundancy, and generate a genotype × environment interaction representative of the targeted market region. The objective was to utilize soybean (Glycine max L.) variety trial results of five relative maturity group (MG) tests at five Tennessee locations spanning 14 yr to compare test location uniqueness and/or redundancy via genetic variance estimates (estimated as twice the genetic variance among homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Different developmental stages responded distinctly to annual weather effects, considering each MG had varying responses to years, which was also observed by Ashworth et al. (2020) with different MG of soybeans. Location‐induced effects were likely owing to different MGs experiencing soil moisture and temperature (day and nighttime) at varying maturity stages, especially tasseling, silking, and grain fill.…”
Section: Resultssupporting
confidence: 77%
See 4 more Smart Citations
“…Different developmental stages responded distinctly to annual weather effects, considering each MG had varying responses to years, which was also observed by Ashworth et al. (2020) with different MG of soybeans. Location‐induced effects were likely owing to different MGs experiencing soil moisture and temperature (day and nighttime) at varying maturity stages, especially tasseling, silking, and grain fill.…”
Section: Resultssupporting
confidence: 77%
“…In a previous study, Ashworth et al. (2020) found that four of the five locations were needed and one location could be eliminated without compromising cultivar yield trial information for five soybean MG tests.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations